Physico-Chemical and Microbial quality of Surface and Ground water Resources in the Obuasi Gold Mining area - Kwarteng, Enock (2014)
A Thesis submitted to the Department of Environmental Science of the Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirement for the degree of Master of Science in Environmental Science.